2018
DOI: 10.1017/s1751731117003147
|View full text |Cite
|
Sign up to set email alerts
|

Dietary l-arginine supplementation improves semen quality and libido of boars under high ambient temperature

Abstract: l-Arginine is a nutritionally essential amino acid for spermatogenesis and plays versatile roles in animal health and can be utilized as a potential agent to improve reproductive performance of boars under high ambient temperature. The present study aimed to determine whether dietary l-arginine could alleviate heat stress-induced infertility in boars. In all, 20 boars (PIC 1040; 248.59±3.84 kg BW and 407.65±6.40 days of age) were selected and randomly assigned to four groups (group 0.0%, basal diet; group 0.6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…In a recent study, Argenti et al (2018) identified increased superoxide dismutase anti-oxidant activity in the sperm of boars raised in sub-tropical Brazil in the summer months probably as a molecular attempt to reduce the presence of ROS and sperm damage (Argenti et al, 2018). Moreover, dietary strategies based on supplementary Zinc (Li et al, 2017) and l-arginine (Chen et al, 2018) have been related to a reduction of oxidative stress and improvement on the epididymal function and boar sperm quality in summer.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, Argenti et al (2018) identified increased superoxide dismutase anti-oxidant activity in the sperm of boars raised in sub-tropical Brazil in the summer months probably as a molecular attempt to reduce the presence of ROS and sperm damage (Argenti et al, 2018). Moreover, dietary strategies based on supplementary Zinc (Li et al, 2017) and l-arginine (Chen et al, 2018) have been related to a reduction of oxidative stress and improvement on the epididymal function and boar sperm quality in summer.…”
Section: Resultsmentioning
confidence: 99%
“…Specific treatments and managerial interventions could help to mitigate or counteract the effects of HS on semen quality. For example, in pigs, dietary supplementation with an essential amino acid such as l ‐arginine could alleviate summer HS (33°C) that resulted in infertility by (a) improving total sperm number and motility; (b) improving semen antioxidant capacity, assessed by a decrease in sperm malondialdehyde and 8‐hydroxy‐2′‐deoxyguanosine content as well as by an increase in the ratio of glutathione to oxidized glutathione, total antioxidant capacity, glutathione peroxidase, and CAT activities in seminal plasma; (c) improving sperm ATP content; (d) preserving mitochondrial ultrastructure; (e) increasing levels of estradiol‐17β and testosterone; (f) improving libido performance (Chen et al, ).…”
Section: Male Reproductive Apparatusmentioning
confidence: 99%
“…Intact, the plasma membrane (IPM) has a negative correlation to MDA and is positively correlated with the viability and motility of spermatozoa. The low dose of L-arginine results in higher viability and motility of spermatozoa; mediated, it increases the antioxidant capacity of semen, which results in a decrease in MDA [29].…”
Section: Ipm and Malondialdehyde Levelmentioning
confidence: 99%